Clinical profile and biochemical abnormalities in Scrub Typhus: A cross-sectional study. (December 2022) - Shrestha, Sanjeeb; Karn, Mitesh; Regmi, Sanjib Mani; Pradhan, Shanti; Nagila, Amar; Prajapati, Rajesh
Abstract: Introduction: Scrub Typhus (ST) is an acute febrile illness caused by obligate intracellular bacteria of the family Rickettsia. It is often unrecognized and neglected but prevalent in tropical regions of endemic areas. The tragedy behind this diagnostic dilemma is non-specific clinical signs and symptoms, limited awareness, unavailability of diagnostic facilities, and low index of suspicion among the physicians. To address the knowledge gap, we tried to find out a proper panel of laboratory investigations to diagnose the disease and predict its progression because of the uncertainty of the course of the disease in a tertiary care hospital in western Nepal. Methods: This is a hospital laboratory-based prospective study conducted at Gandaki Medical College- Teaching Hospital (GMC-TH) for a period of two years. Among 988 cases of acute febrile illness, 40 seropositive cases of ST were enrolled in the study. We excluded those who did not give consent for the participation, those who were under 17 years of age, and those who had preexisting liver dysfunctions and other co-morbidities and dual seropositive with other infectious etiologies. We used descriptive statistics to analyze the data in terms of demography, clinical features, and laboratory parameters. Results: Out of 988 febrile patients, we included 40 confirmed cases of ST aged between 17 and 70 years during the study-period. Maximum seropositive cases were from Tanahun district 14 (35%), with predominance among the women (70%). The cases were prevalent in the age group 30–60 years, 19 (47.5%), and in the month of October 15 (37.5%). The commonest complaints were fever in 40 (100%), headache in 20 (50%), eschar in 11 (27.5%). Laboratory parameters showed anemia in 22 (55%), hypoalbuminemia in 11 (27.5%), leukopenia in 5 (12.5%), leukocytosis in 9 (22.5%), thrombocytopenia in 13 (32.5%), raised transaminase levels, SGPT in 21 (52.5%) and SGOT in 14 (26%) ST patients. Conclusion: We found clinical and laboratory profiles in patients with ST were varied and nonspecific. However, knowledge of these findings may evoke the recognition of ST and give a clue to the progression of the disease. Highlights: ST is endemic to Nepal but usually misdiagnosed due to non-specific symptoms and limited laboratory facilities. Higher prevalence during the post-monsoon period coincides with the growth of scrub vegetation which is a habitat for mites. Higher transaminase levels, hypoalbuminemia, leukocytosis, leukopenia, and thrombocytopenia are predictors of multi-organ dysfunction.